Learning media using Pop-up Book "Variety of traditional houses in Indonesia" as alternative media in Pancasila Education for primary school - Rofiah, Nurul Hidayati; Budiyono, Budiyono; Dewi, Rahmatika (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
The research process involved creating a pop-up book for Pancasila Education, explicitly focusing on the physical diversity of traditional Indonesian houses. The study used the comprehensive ADDIE model for research and development, involving thorough analysis, design, development, implementation, and evaluation. Data collection techniques included qualitative and quantitative methods. The results showed that the pop-up books were of high quality, with media experts assessing them at 87.1, material experts at 83.3, learning experts at 73.3, and linguists at 81.7. Field-tested, the book received high scores from teachers and students at 98.0 and 93.3, respectively. The overall score was 91.0, indicating its high quality. The pop-up book can be a valuable tool for boosting students' enthusiasm and interest in learning and achieving goals optimally.